Modalities of case assignment: The view from Lithuanian - Lavine, James E. (Vilnius University Open Series, 2021)
This paper assesses two competing modalities for the assignment of morphological case. Arguments are provided from Lithuanian against the configurational strategy of Dependent Case (Marantz 1991, Baker 2015) and in favor of case assignment by functional heads (Chomsky 2000, 2001). The first argument comes from a series of Transitive Impersonal constructions in which accusative appears independently, in the absence of a higher, nominative-marked argument, so long as the predicate is two-place and caused, implicating v-Cause as the source of accusative. Further evidence for this analysis comes from the Inferential Evidential, an oblique-subject construction. While the Dependent Case strategy states that nominative automatically shifts to the object if not assigned to the subject, nominative objects are exceedingly rare in the Inferential Evidential, a fact that is entirely consistent with the local, feature-based theory of case advanced in this paper, which relates the appearance of nominative to the Agree relation with Tense.